2019
DOI: 10.17140/vmoj-4-137
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Value of Croton macrostachyus and Solanum incanum against Causative Agent of Foodborne Diseases

Abstract: Cite this articleAbdisa T. Medicinal value of Croton Macrostachyus and Solanum Incanum in treatment of foodborne diseases. Vet Med Open ABSTRACT Copyright 2019 by Abdisa T. This is an open-access article distributed under Creative Commons Attribution 4.0 International License (CC BY 4.0), which allows to copy, redistribute, remix, transform, and reproduce in any medium or format, even commercially, provided the original work is properly cited. 57Review | Volume 4 | Issue 2| cc Foodborne diseases are a public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…One of the largest species in the family Euphorbiaceae and subfamily Crotonaceae, Croton macrostachyus, is a native plant to Ethiopia, Eritrea, Uganda, Kenya, Tanzania, and Nigeria. It is used to treat a variety of illnesses affecting human health [29].…”
Section: Introductionmentioning
confidence: 99%
“…One of the largest species in the family Euphorbiaceae and subfamily Crotonaceae, Croton macrostachyus, is a native plant to Ethiopia, Eritrea, Uganda, Kenya, Tanzania, and Nigeria. It is used to treat a variety of illnesses affecting human health [29].…”
Section: Introductionmentioning
confidence: 99%
“…Croton macrostachyus is called rush foil in English, Bakkaniisa in Afan Oromo, and Bisana in Amharic. Literature reported that the genus croton is rich in terpenoids, alkaloids, flavonoids, lignoids, proanthocyanidins, saponins, cardiac glycosides, and tannin compounds. The fruits, leaves, and roots of Croton macrostachyus are used as medicine in various human and animal diseases. Traditionally, this plant is used for the remedy of diverse sickness such as malaria, gonorrhea, rabies, diarrhea, abdominal pain, typhoid, pneumonia, and gastrointestinal disorders. …”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, this plant is used for the remedy of diverse sickness such as malaria, gonorrhea, rabies, diarrhea, abdominal pain, typhoid, pneumonia, and gastrointestinal disorders. 29 32 …”
Section: Introductionmentioning
confidence: 99%
“…It is a perennial shrub-like herb with small prickles on the leaves and stems that can grow up to 1.8 meters. When ripe, the fruits are small berries that measure 2–3 cm in diameter and are yellowish orange or brown in color [ 12 , 13 ]. It is a very common shrub in Ethiopia, where it can be found on abandoned agricultural lands, along roadsides, and in village yards.…”
Section: Introductionmentioning
confidence: 99%
“…It is a very common shrub in Ethiopia, where it can be found on abandoned agricultural lands, along roadsides, and in village yards. The plant has several local names in Ethiopia: Embuay (in Amharic) and Hiddii (in Oromifa) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%